PELATIHAN PERBANYAKAN Trichoderma sp. DALAM PENGENDALIAN PENYAKIT BAWANG MERAH DI PADUKUHAN GROGOL X, PARANGTRITIS, YOGYAKARTA - Wisnubroto, Muhammad Parikesit; Puspitasari, Herlina Mega; HP, Julsento (Universitas Padjadjaran, 2026)
Padukuhan Grogol X is part of Parangtritis Village, Bantul, Yogyakarta, where most of the people work as farmers. Shallots are one of the most widely cultivated crops in this area. The biggest obstacle in cultivating this crop is fusarium wilt and purple spot (trotol) disease, which cause a decrease in yield. Both diseases are caused by the fungi Fusarium sp. and Alternaria porii, respectively. Control measures so far have been carried out chemically using synthetic fungicides. Chemical control is the predominant method of disease management in this area. This community service activity aims to educate shallot farmers about the importance of biological control and provide training in the propagation of the biological agent Trichoderma sp. using simple, easily obtainable materials. The equipment and materials prepared include socialization tools, containers, Trichoderma sp. isolates, newsprint, and half-cooked rice. The Trichoderma sp. isolate is mixed with half-cooked rice, then placed into a container, sealed, and left for 1–2 weeks. The resulting product can be used as a biological agent to control Fusarium sp. and A. porii. During the socialization and training process, farmers were quite enthusiastic and attentive to the material presented. After the assistance, farmers gradually began to reduce the intensity of chemical disease control and started substituting it with Trichoderma sp., which they propagated independently.Padukuhan Grogol X merupakan bagian dari Kelurahan Parangtritis, Bantul, Yogyakarta yang sebagian besar penduduknya berprofesi sebagai petani. Tanaman bawang merah menjadi salah satu jenis tanaman yang paling banyak dibudidayakan pada daerah ini. Kendala terbesar dalam budidaya tanaman tersebut antara lain disebabkan oleh serangan penyakit layu fusarium dan bercak ungu/trotol yang menyebabkan penurunan hasil panen. Kedua penyakit tersebut masing-masing disebabkan oleh cendawan Fusarium sp. dan Alternaria porii. Adapun pengendalian secara kimiawi merupakan jenis pengendalian penyakit yang dominan pada daerah ini. Kegiatan pengabdian masyarakat ini bertujuan untuk memberikan edukasi kepada petani bawang merah akan pentingnya pengendalian hayati serta pelatihan perbanyakan agen hayati Trichoderma sp. dari bahan sederhana yang mudah diperoleh. Peralatan dan bahan yang dipersiapkan antara lain peralatan sosialisasi, wadah, isolat Trichoderma sp, kertas koran, dan beras/nasi setengah matang. Isolat Trichoderma sp. dicampurkan dengan nasi setengah matang kemudian dimasukkan ke dalam wadah, lalu ditutup dan ditunggu hingga 1–2 minggu. Hasil yang diperoleh dapat digunakan sebagai agen hayati pengendali Fusarium sp. dan A. porii. Selama proses sosialisasi dan pelatihan, petani cukup antusias dan menyimak materi yang disampaikan. Setelah dilakukan pendampingan, petani secara perlahan mulai mengurangi intensitas pengendalian penyakit secara kimiawi dan mulai mensubstitusinya menggunakan Trichoderma sp. yang telah diperbanyak secara mandiri.